Pengaruh Efikasi Diri terhadap Kesiapan Kerja Mahasiswa Akhir Program Studi Manajemen Angkatan 2018 Fakultas Ekonomi dan Bisnis Universitas Islam Bandung - Syafira Yasinta; Aminuddin Irfani (UNISBA Press, 2022)
Abstract. Many companies require contributions from potential human resources and many of them are looking for prospective undergraduate graduates who have been confirmed to have work skills in the form of self-efficacy and good work readiness, especially human resource management graduates who know the knowledge to manage the goals of a company or organization can be achieved. This study aims to 1) To find out how the self-efficacy of the final students of the management Study Program class of 2018 at the Faculty of Economics and Business, Islamic University of Bandung. 2) To find out how the work readiness of the final students of the management study program class of 2018 at the Faculty of Economics and Business Unisba has. 3) To find out how the effect of self-efficacy on the work readiness of final year students of the management tudi program class of 2018 at the Faculty of Economics and Business, Islamic University of Bandung. The research method used is descriptive and verifiable analysis. Methods of collecting data obtained through interviews and questionnaires. The respondents in this study were 166 final management students of the class of 2018. Purposive sampling technique with slovin formula. The results of this study concluded that: 1) Self-efficacy in the final students of the management study program namely the results are